Effects of household composition on infant feeding and mother–infant health in northern Kenya - Vankayalapati, A.; Wamwere-Njoroge, George J.; Fujita, M. (Wiley, 2024)
Background Households with alloparents, individuals other than the mother who care for an infant, can shift members' roles and affect mother–infant health.